CONCENTRATION OF ORANGE JUICE BY USING POLYMERIC DEHYDRATION TO PROTECT FLAVOR COMPOUNDS - Khattab , Mohammed Subhi; Musa, Tariq Nasser (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This article is an attempt to protect the main flavor compounds in concentrated orange juice by using polymeric dehydration techniques (sodium polyacrylate), instead of the traditional which causes a remarkable degradation in these compounds. The physiochemical and microbial properties of juice were monitored throughout the concentration processes. Polymeric dehydration was used at different conditions to concentrate orange juice and comparing with traditionally heat treatment. Total soluble solid (TSS), ascorbic acid, acidity, pH, viscosity and tannins have been affected by various levels according to concentration technique and period of storage. The microbial content had never developed even throughout the storage for six months, because 100 ppm sodium benzoate was added to the fresh juice immediately after squeezing. The main flavor compounds in fresh orange juice have been monitored throughout the various concentration processes to evaluate their abilities for maintaining the flavor compounds of concentrated juice